Analysis of Theobromine and Related Compounds by Reversed Phase High-Performance Liquid Chromatography with Ultraviolet Detection: An Update (1992–2011) - Sandra Aparecida de Assis; Amanda Reges de Sena; Alexsandro Branco (Food Technology and Biotechnology, 2011)
Theobromine and its related compounds, such as caffeine and theophylline, are secondary metabolites that belong to the alkaloids and have economic and cultural importance. These alkaloids have demonstrated stimulatory effects on the central nervous, gastrointestinal, cardiovascular, renal and respiratory systems, resulting in 'energy arousal', increased motivation to work, increased alertness and increased cognitive function. Several analytical methods have been used to analyse these compounds, but reversed phase high-performance liquid chromatography (RP-HPLC) is the most commonly applied because of its efficiency, sensitivity, specificity and speed. This review describes the analyses of theobromine-related compounds by RP-HPLC with ultraviolet detection (UV) in four sources: food, beverages, biological fluids and plants. Many RP-HPLC methods have been developed and optimized for the detection and quantification of these natural compounds. Elution under isocratic conditions is the most frequent method, with a water, methanol and acetonitrile mixture modified with acetic, phosphoric or formic acid as the mobile phase. For xanthine analysis, the use of reversed phase high-performance liquid chromatography with an ultraviolet/diode array detector (UV/DAD) is particularly suitable as derivation is not required; it allows the analysis of absorbance at all wavelengths, it is simple and rapid.